Paul and Diversity A New Perspective on Σάρξ and Resilience in Galatians - Joelsson, Linda (Routledge Interdisciplinary Perspectives on Biblical Criticism, 2024)
This book investigates attitudes toward diversity as expressed in Paul's letter to the Galatians and proposes a renewed understanding of the term σάρξ as used in this letter. Σάρξ (sarx) is usually translated as "flesh" and has often been perceived in theological studies as a complicated and highly polysemous term. It is also a word whose interpretations have had far-reaching social, political, and religious consequences throughout history. The author argues in this volume that for Paul the term σάρξ is commonly adopted with reference to the collective group, and in light of a sense of collective identity in particular. A key assertion is that Paul was and remained a Jew and also continued to be deeply concerned with the prospects for the peaceful co-existence of Jews and Gentiles in the assemblies of God. The chapters draw on perspectives from classical rhetoric, modern linguistics, and social systems theory in order to describe the communicative structure of the letter, the construct of collective identity as described within this setting, and the potential for resilience in this construct. Offering a more coherent reading of Galatians, the book contributes positively to current discussions in Pauline studies and will be of interest to scholars of biblical studies and theology.